KINDS OF PREPOSITION IN QURAN SURAH YASIN - YUSNI SINAGA M.HUM (JURNAL LINER (Language Intelligence and Educational Research), 2021)
As al-qur’an is a book of guidance for muslims. Must be studied by all muslims. Muslims’followers can be found in most of countries in this world that’s why the al-quran can be found in most of countries in this world. Look at to this cases al-quran needed to be translated to be analized in most of languages found in this world. It cuased of the al-quran it self only printed in Arabic language. Islam or muslim is one of the internasional religion because the followers can be found most of in every country in the world, so Al-quran is the holy book (kibatullah) of the islam so Al-quran is the one of the internasional religion. Al-quran stated by Allah SWT I and obligated to obey or to do n Arabic language, al-quran contents all found in the world means all things in the universe. All its followers obligated to study, to know the content and obligated to obey or to do the messages in it because the al-quran orders its followers own good character means the best references for the good character can be seen in al-quran. Because of can not be said that all people can speak Arabic language in this word show that the al-quran must be translated to many languages in this wolrd such as in Indonesia, Duetch , German, French, Japan, English, etc .